Clinical course of spinal pain in adolescents: a feasibility study in a chiropractic setting - Steven J Kamper; Christopher G Maher; Mark J Hancock; Simon D French; Lise Hestbæk; Katherine A Pohlman; Michael S Swain; Laura RC Montgomery; Anika Young; Amber Beynon (BMJ Open)
Design Prospective feasibility study.Objectives To inform the design and conduct of a large-scale clinical cohort study investigating adolescents with moderate-to-severe spinal pain.Setting Chiropractic care in Sydney, Australia.Participants Adolescents aged 12–17 years with spinal pain (≥4/10 pain intensity score).Methods Adolescents and chiropractors completed baseline and week-12 follow-up questionnaires, with adolescents reporting pain intensity and recovery weekly via text messages during weeks 1–11. Questionnaire measures included spinal pain, pain coping, quality of life, physical activity, clinical assessment findings and care delivered. Chiropractors provided usual clinical care. We conducted a descriptive feasibility analysis.Primary outcomes (1) Recruitment rate, (2) response rate to each data collection instrument and (3) retention rate.Results From May 2021 to February 2023, 20 chiropractors from 10 clinics were enrolled (invited n=85). 10 chiropractors recruited 45 adolescents (15.4±1.4 years, 43% female) over 13.5 months, excluding an 8-month pause due to COVID-19 disruptions. The average recruitment rate was 0.6 adolescents/recruiting chiropractor/month. We achieved a 100% response to chiropractor baseline and follow-up questionnaires, 98% to adolescent baseline, 94% average response to combined weekly text messages and 93% retention of adolescents at study completion.Conclusions Our high response and retention rates demonstrate feasible data collection methods in this population. Addressing low recruitment by expanding the number and type of clinicians is necessary for a successful larger study.